Student evaluation of teaching effectiveness: implications for scholars in operations management - Duarte de Almeida, I.; Silva, J. M.; Möhring, M. M. (25th EurOMA – To Serve, to Produce and to Servitize in the Era of Networks, Big Data, and Analytics, 2018)
Many times, teaching rating by students are the most influential measure of the quality of teaching departments, courses and teachers to assess how curricula changes are perceived by students. This study seeks biases introduced by background variables. If these are relevant, then student evaluations as a valid indicator of teaching effectiveness for the purpose of quality improvement and assurance could be questioned. The research purpose is (i) to appreciate the suitability of business student ratings in assessing teaching performance, and (ii) to explore limitations of current practices considering student evaluation as a primary university tool to assess teaching effectiveness.